2021
DOI: 10.9734/jpri/2021/v33i26a31470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidiabetic Activity of a Novel Polyherbal Preparationagainst Streptozotocin Induced Diabetes Rat Model

Abstract: Background: Diabetes Mellitus is a chronic disorder characterised by abnormally elevated glucose levels in the blood. Diabetes is caused by one of two mechanisms: insufficient insulin synthesis (which is produced by the pancreas and reduces blood glucose) or insufficient response of cells to insulin action. The current aim of this research project was to formulate and evaluate the Polyherbal preparation (PHP) of the plants constituted with Cinnamonum zeylanicium (CJ) bark, Eugenia jambolana (EJ) seeds, Vinca r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Interestingly, treatment with the extract resulted in significant improvements in lipid profile: at 4 weeks, serum TC, TGs, VLDL-C, and LDL-C had reduced and were able to enhance HDL-C levels. These findings also correlate with those of Tsofack et al 47 and Jyothsna et al, 44 who (respectively) reported that D. picta and Cinnamomum zeylanicum reduced cholesterol and TGs in experimentally induced diabetic rats. This activity of the plant extract may be related to the presence of secondary metabolites implicated in the antihyperlipidemic activity of plant extracts.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, treatment with the extract resulted in significant improvements in lipid profile: at 4 weeks, serum TC, TGs, VLDL-C, and LDL-C had reduced and were able to enhance HDL-C levels. These findings also correlate with those of Tsofack et al 47 and Jyothsna et al, 44 who (respectively) reported that D. picta and Cinnamomum zeylanicum reduced cholesterol and TGs in experimentally induced diabetic rats. This activity of the plant extract may be related to the presence of secondary metabolites implicated in the antihyperlipidemic activity of plant extracts.…”
Section: Discussionsupporting
confidence: 90%
“…The chief source of energy in animals body is glucose, and the oral glucose-tolerance test (OGTT) enables us to evaluate the body's capacity to use glucose wisely. 44 A single dose of crude extract was administered to normoglycemic mice to verify its antihyperglycemic activity. OGTTs with 40% glucose solution resulted in hyperglycemia with a peak of 179.51 ±2.29 mg/dL 30 minutes after administration in the negative-control group, but that peak was significantly averted by both the standard drug (Glc5) and the crude extract at all test doses (P<0.001, see Table 4).…”
Section: Effect Of Extract On Oral Glucose Tolerance In Micementioning
confidence: 99%
“…The findings of present study are similar with the findings of others that demonstrated the substantial antihyperglycemic properties of polyherbal formulation in STZ induced diabetic rats. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Our findings are similar with the findings of other authors. It has been demonstrated that our discoveries can decrease blood sugar levels in diabetic animals.…”
Section: Body Weight Of Ratssupporting
confidence: 91%